Peer Culture and Body Image Concern Among Australian Adolescent Girls: A Hierarchical Linear Modelling Analysis - Carey, Renee; Donaghue, N.; Broderick, P. (2013)
Peers may influence the body image concerns and disordered eating behaviours of adolescent girls through the creation of appearance cultures within friendship cliques. The present study investigates the role of friendship cliques and school gender composition in impacting upon adolescent girls' body image concern and disordered eating behaviours, using hierarchical linear modelling (HLM), a statistical procedure employed in the analysis of nested data. A sample of 156 girls was drawn from four private schools located in the capital city of Western Australia (one single-sex school and three mixed-sex schools). Eighty students from the single-sex school and 76 female students from the mixed-sex schools, comprising 35 friendship cliques, completed questionnaires assessing body image, disordered eating, and a range of variables that have previously been associated with body image concern and disordered eating, including appearance-based social comparison, frequency of appearance-based conversation, appearance-based criticism, friends' concern with thinness, media influence and media pressure. Hierarchical linear modelling analyses found that friendship cliques in all-girls schools exhibited similar levels of body image concern and dieting behaviours, with various peer and other media influence variables accounting for these similarities. Friendship cliques in mixed-sex schools were not found to be similar with regard to body image concern or disordered eating. These findings support the notion that friendship groups can be an important source of influence on the body image concerns of adolescent girls in single-sex schools, and show that both individual and friendship clique level measures of attitudes and behaviours make independent contributions to the prediction of these body image concerns. © 2013 Springer Science+Business Media New York.